Globalization and Higher Education: Opportunities for Russia - M. V. Kharkevich (Vestnik MGIMO-Universiteta)
The article reviews the content of academic discourse on higher education and globalization. It posits that according to the discourse under globalization the higher education has developed such properties as being transnational, self organizing through networks and commercialized. It also stresses that strategic development and stratification of universities are best understood through the concept of university as a positional good. For the Russian higher education the article suggests moving away from ideas of new public management to governance. Such a step should provide for internationalization of Russian higher education while preserving it as a public good with its national character and traditions.